Sudden cardiac death in the soccer field: a retrospective study in young soccer players from 2000 to 2013 - Davogustto, G.; Higgins, J. (The Physician and Sportsmedicine, 2014)
Soccer is the most popular sport in the world, with over 200 million active players. Sudden cardiac death (SCD) represents the most striking as well as the most common cause of death in the soccer field. Underlying cardiovascular pathologies predispose to life threatening ventricular arrhythmias and SCD in soccer players. Up to thousands to hundred thousands players might have an underlying condition that predisposes them for SCD. After several media striking SCD events in soccer players the Fédération Internationale de Football Association (FIFA) has made screening recommendations that are more thorough than the ones recommended for the American Heart Association and the European Society of Cardiology. We present a retrospective search through Internet databases that resulted in 54 soccer players with SCD events from 2000 until 2013. In this article, we will describe and discuss the conditions of those cases of SCD in order to provide more knowledge of the factors that may precipitate SCD in young soccer players.